Belanja online menjadi trend remaja selama pandemi covid-19 - Sari Utami (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2020)
The COVID-19 pandemic which requires everyone to stay at home, beginning with working (Work from House), studying (school), trading, or even hanging out with friends, are very difficult nowadays. The pandemic in Indonesia has now entered a serious stage and forces the government to implement PSBB (Large-scale Social Restrictions) in some provinces and regions. Not only does it limit everyone to interact or communicate directly, but this program also indirectly makes every shop or cafe closed or limited to do transactions. Covid-19 pandemic has succeeded in accelerating and even forcing business transformation such as food and drinks and selling activities from traditional to online through the principle of digitalization. Presently, all parties are forced to do online activities and apply the principle of digitalization, otherwise economic and business activities will die. This article uses a descriptive qualitative analysis method that looks at the phenomena of online trading transactions during the Covid-19 pandemic. Among the various transaction users (online shopping) at this time, teenagers share a variety of creativity and do not feel run out of ideas while staying at home, they choose to use food delivery services related to their consumptive nature and also order and shop online to buy an item or deliver goods without leaving the house by doing online transactions and transferring payments or Cash on Delivery (COD). The millennial generation will not feel limited or restricted during this pandemic. Since basically, being a digital native is their nature, therefore when everything has to be done digitally without having to get involved directly they will remain productive.Pandemi COVID-19 yang mengharuskan semua orang untuk tinggal di rumah, dimulai dengan bekerja (Work from House), belajar (sekolah), berdagang, atau bahkan bergaul dengan teman-teman, sangat sulit saat ini. Pandemi di Indonesia saat ini telah memasuki tahap serius dan memaksa pemerintah menerapkan PSBB (Pembatasan Sosial Berskala Besar) di beberapa provinsi dan daerah. Tidak hanya membatasi semua orang untuk berinteraksi atau berkomunikasi secara langsung, program ini juga secara tidak langsung membuat setiap toko atau kafe tutup atau terbatas untuk melakukan transaksi. Pandemi Covid-19 telah berhasil mempercepat dan bahkan memaksa transformasi bisnis seperti makanan dan minuman serta kegiatan jual dari tradisional ke online melalui prinsip digitalisasi. Saat ini, semua pihak terpaksa melakukan kegiatan online dan menerapkan prinsip digitalisasi, jika tidak, kegiatan ekonomi dan bisnis akan mati. Artikel ini menggunakan metode analisis kualitatif deskriptif yang melihat fenomena transaksi perdagangan online selama pandemi Covid- 19. Di antara berbagai pengguna transaksi (belanja online) saat ini, remaja berbagi berbagai kreativitas dan tidak merasa kehabisan ide selama tinggal di rumah, mereka memilih untuk menggunakan layanan pesan- antar makanan yang berkaitan dengan sifat konsumtif mereka dan juga memesan dan berbelanja online untuk membeli barang atau mengirimkan barang tanpa meninggalkan rumah dengan melakukan transaksi online dan mentransfer pembayaran atau Cash on Delivery (COD). Generasi milenial tidak akan merasa terbatas atau dibatasi selama pandemi ini. Karena pada dasarnya, menjadi digital native adalah sifat mereka, oleh karena itu ketika semuanya harus dilakukan secara digital tanpa harus terlibat langsung mereka akan tetap produktif.